Penerapan Model Pelayanan Maternitas One Student One Client Sebagai Upaya Pencegahan Kematian Ibu Dan Bayi Di Kabupaten Kendal - Shinta Ika Sandhi; Masruroh - Akademi Kebidanan Uniska (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2018)
Abstact: Kendal District Mother's 3-year Mortality Rate from 2012 shows a fructuative condition. The One Student One Client maternity model is expected to reduce maternal and infant mortality through qualified and professional midwives generated by qualified health institutions. The design of this study using. The data was collected by questionnaire and observation on the midwife and student in Kendal District Health Office. Application of Maternity Services